Galectin-3 is associated with the functional outcome and mortality in stroke patients: A systematic review and meta-analysis. Issue 2 (February 2023) - Han, Xiaoling; Geng, Bingbing; Deng, Feiyan; Ma, Ying; Fan, Ningning; Huang, Shaomin; Xue, Ming; Wu, Lei; Li, Bixia; Liao, Shaoqin; Ye, Qiao; Liu, Yu
Abstract: Introduction: There is still a lack of sensitive predictive tools for stroke outcomes. High galectin-3 concentration is associated with an increased risk of stroke. This study investigated the relationship between blood galectin-3 levels and stroke prognosis. Methods: The PubMed, EMBASE, and Cochrane Library databases were searched as of May 2021. Data from eligible studies on the relationship between galectin-3 and stroke prognosis were extracted for the meta-analysis. Results: The outcomes included the modified Rankin Scale (mRS), mortality rate, and prognostic accuracy of galectin-3 on mRS after stroke. Odds ratio (OR) and 95% CI were used to assess the association between galectin-3 and the prognostic outcomes. Subgroup analysis based on the study design was performed to evaluate the correlation of galectin-3 with mRS and mortality. A random-effects model was adopted for this meta-analysis. A total of 5 studies involving 3607 stroke patients were included. Higher serum galectin-3 level was associated with mRS (OR [95% CI]: 2.02 [1.08, 3.77]) and mortality (OR [95% CI]: 2.17 [1.17, 4.02]) after stroke. Subgroup analysis revealed a similar relationship between galectin-3 and mRS for both prospective and retrospective studies. There were no associations between galectin-3 level and mortality rate in prospective studies. Galectin-3 had a good predictive ability on mRS after stroke (AUC: 0.88, 95% CI:0.85, 0.91). Conclusion: Elevated blood galectin-3 levels were associated with prognostic outcomes after stroke, including functional outcome mRS and mortality rate. Moreover, galectin-3 had a good predictive ability for the prognosis of stroke.